2018
DOI: 10.3390/md16100366
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antibiofilm Activity of a Recombinant Fragment of β-Thymosin of Sea Urchin Paracentrotus lividus

Abstract: With the aim to obtain new antimicrobials against important pathogens such as Staphylococcus aureus and Pseudomonas aeruginosa, we focused on antimicrobial peptides (AMPs) from Echinoderms. An example of such peptides is Paracentrin 1 (SP1), a chemically synthesised peptide fragment of a sea urchin thymosin. In the present paper, we report on the biological activity of a Paracentrin 1 derivative obtained by recombination. The recombinant paracentrin RP1, in comparison to the synthetic SP1, is 22 amino acids lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Marine organisms are a very important source of antimicrobial agents (Richards et al, 2001;Schillaci et al, 2010;Schillaci et al, 2013;Spinello et al, 2018;Vazzana et al, 2018;Núñez Acuña et al, 2018) and, among them, the PUFAs are normally present at high levels in Salmo salar (Linder, Fanni & Parmentier, 2005;Morais et al, 2009). Different studies have shown the antimicrobial activity of the salmon PUFAs against Gram-positive bacteria due to their specific components such as eicosapentaenoic acid (Desbois, Mearns-Spragg & Smith, 2009;Desbois & Lawlor, 2013), docosahexaenoic acid (Coonrod, 1987;Feldlaufer et al, 1993;Gladyshev et al, 2009), γ-linolenic acid (Asthana et al, 2006) and dihomoγ-linolenic acid (Feldlaufer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Marine organisms are a very important source of antimicrobial agents (Richards et al, 2001;Schillaci et al, 2010;Schillaci et al, 2013;Spinello et al, 2018;Vazzana et al, 2018;Núñez Acuña et al, 2018) and, among them, the PUFAs are normally present at high levels in Salmo salar (Linder, Fanni & Parmentier, 2005;Morais et al, 2009). Different studies have shown the antimicrobial activity of the salmon PUFAs against Gram-positive bacteria due to their specific components such as eicosapentaenoic acid (Desbois, Mearns-Spragg & Smith, 2009;Desbois & Lawlor, 2013), docosahexaenoic acid (Coonrod, 1987;Feldlaufer et al, 1993;Gladyshev et al, 2009), γ-linolenic acid (Asthana et al, 2006) and dihomoγ-linolenic acid (Feldlaufer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The cellular response is mediated by a particular class of cells, the coelomocytes, that circulate in the coelomic cavity and can infiltrate tissues and organs being the first mediators of allograft rejections; they act, through different activating pathways [4,6,15,28,29] in response to host invasion, injury and cytotoxic agents. The humoral response is mainly due to molecules like lectins, cytokines and profilins, to the complement system and antimicrobial peptides [30][31][32]. For the purpose of this study, we treated Paracentrotus lividus sea urchins with LPS, at different exposure times, to induce an immunological response, and then, through a label free mass spectrometry approach, we analyzed the protein expression pattern to identify mechanisms, processes and pathways involved in the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Sea cucumber are the most studied group and represent an excellent source of triterpene glycosides, the whose effects are widely confirmed in the literature [95,96,97]. Further, sea urchins have been the object of several studies, which have revealed the potential of biomolecules such as antimicrobial peptides [98,99,100]. Within this context, starfishes found clearly their considerable position among echinoderms because of the biological potential of their derived compounds.…”
Section: Discussionmentioning
confidence: 99%